A Simple and Rapid Method for Quantitative HPLC MS/MS Determination of Selected Perfluorocarboxylic Acids and Perfluorosulfonates in Human Serum - Valentina Marra; Annalisa Abballe; Elena Dellatte; Nicola Iacovella; Anna Maria Ingelido; Elena De Felip (International Journal of Analytical Chemistry)
Per- and polyfluorinated alkyl substances (PFASs) are ubiquitous environmental contaminants, present in the environment and in the human body. They have raised global concern because of their diffusion in the environment, particularly in water, causing cases of human overexposure due to consumption of contaminated drinking water. Human biomonitoring is the most effective way to characterize human exposure to PFASs, and it is important that as many labs as possible could easily perform this kind of analysis. Analytical methods for quantitation of PFAS mixtures in human serum have been developed, but most of them required materials that are not always easily available in all the laboratories. This paper describes a very simple and accessible HPLC MS/MS method of analysis and quantification of 13 perfluorocarboxylic acids and perfluorosulfonate compounds (belonging to the class of per- and polyfluorinated alkyl substances (PFASs)) in human serum. Method development data provide detailed descriptions of the optimization process in terms of sample preparation, laboratory analysis of human serum samples, determination of analytes by HPLC MS/MS, and describing the pump gradient time, working conditions, and acquisition.